Ionic mass transfer on fixed disk and conical electrodes under streaming solutions : II. Experimental approach - Carrozza, Jesús Simón (1967)
Ionic mass transfer on conical electrodes with axially streaming solutions is studied. The limiting current for different electrochemical systems was determined under experimental conditions chosen for testing the conclusion of the previous theoretical study. The intluence of the flow rate, the length of the cone, the angle of the cone, the viscosity of the fluid, the diffusivity of the component as well as the ratio of the maximum cone diameter to the width of the channel was determined. The average rate equation under laminar conditions, is expressed by the dimensionless equation Shx = 0·80 Rex1/2Sc/13, where Xrefers either the cone genera& or the radius of the disk-type electrode chosen as the characteristic length, the Reynolds number being detined by means of the maximum flow rate. Experimental data agree with the theoretical prediction.